Mechanism of signal sequence handover from NAC to SRP on ribosomes during ER-protein targeting - Jomaa, Ahmad (Science, 2022)
The nascent polypeptide-associated complex (NAC) interacts with newly synthesized proteins at the ribosomal tunnel exit. NAC competes with the signal recognition particle (SRP) to prevent mistargeting of cytosolic and mitochondrial polypeptides to the endoplasmic reticulum (ER). How NAC antagonizes SRP and how this is overcome by ER targeting signals is unknown. Here, we found that NAC uses two domains with opposing effects to control SRP access. The core globular domain prevented SRP from binding to signal-less ribosomes, whereas a flexibly attached domain transiently captured SRP to permit scanning of nascent chains. The emergence of an ER targeting signal destabilized NAC’s globular domain and facilitated SRP access to the nascent chain. These findings elucidate how NAC hands over the signal sequence to SRP and imparts specificity of protein localization.